The Relationship between Parent-reported PEDI-CAT Mobility and Gross Motor Function in Children with Cerebral Palsy: Brief Report. - Lewis, Jessica; Scott, Kimberley; Pan, Xueliang; Heathcock, Jill (Developmental Neurorehabilitation, 2020)
Purpose: The PEDI-CAT mobility domain (PEDI-mob) is a parent-reported measure of mobility for children up to 21 years of age. The purpose of this research is to investigate the relationship between the PEDI-mob and Gross Motor Function Measure (GMFM)-66 and Gross Motor Function Classification Scale (GMFCS) levels. Methods: Fifty-seven children (N = 57), ages 2–8.8 years participated. PEDI-mob and GMFM were administered and GMFCS was confirmed during the same session. A Pearson correlation coefficient was calculated for PEDI-mob and GMFM-66 scores to evaluate the association between these two measures. An ANOVA was used to analyze PEDI-mob across GMFCS levels. Results: Large, statistically significant correlation was found between PEDI-mob and GMFM-66 scores (r = 0.894, p-value<0.001). Differences in PEDI-mob scores were found across GMFCS levels (p-value <0.001), where patients with higher GMFCS levels had lower PEDI-mob scores. Conclusion: These results support a strong relationship between parent-reported and clinically measured motor function.